2017
DOI: 10.2298/jsc170422066b
|View full text |Cite
|
Sign up to set email alerts
|

Removal of heavy metals from water using multistage functionalized multiwall carbon nanotubes

Abstract: The multistage synthesis of the multi-wall carbon nanotubes (MWCNT) modified with polyamidoamine dendrimers, A1/ and A2/MWCNT, capable of cation removal, is presented in this work, as well as novel adsorbents based on these precursor materials and modified with goethite nano-deposit, α-FeOOH, A1/ and A2/MWCNT-α-FeO(OH) adsorbents used for As(V) removal. In a batch test, the influence of pH, contact time, initial ion concentration and temperature on adsorption efficiency were studied. Adsorption data modelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…At higher pH values, the decreased adsorption capacity by Cd(II) coincides with the decreasing concentration of Cd(II) and the precipitation of Cd(OH) 2 into solution. The Cd(OH) 2 ionic species are adsorbed by the MAAC beads occupying the available sites and preventing the further adsorption of Cd(II) ions [21]. For nickel an increasing trend at higher pH values was observed.…”
Section: Effect Of Phmentioning
confidence: 95%
“…At higher pH values, the decreased adsorption capacity by Cd(II) coincides with the decreasing concentration of Cd(II) and the precipitation of Cd(OH) 2 into solution. The Cd(OH) 2 ionic species are adsorbed by the MAAC beads occupying the available sites and preventing the further adsorption of Cd(II) ions [21]. For nickel an increasing trend at higher pH values was observed.…”
Section: Effect Of Phmentioning
confidence: 95%
“…E. M. Elsehly et al 207 reported the use of functionalized carbon nanotubes for fabrication of filters to remove chromium from aqueous solutions. Removal of heavy metals from water by using multistage functionalized multiwall carbon nanotubes has been reported by D. Budimirović et al 208 In a recent report by M. M. Aslam et al 209 the preparation and application of f-CNTs for water and wastewater treatment have been reviewed. It was observed that, functionalized CNTs have proven to be a promising nanomaterial for the decontamination of water particularly due to their high adsorption capacity.…”
Section: Applications Of Functionalized Cntsmentioning
confidence: 99%
“…18 According to the nature of this method, the key point is choosing a suitable sorbent, since this factor could affect the selectivity and sensitivity of the method. 19 With the advent of SPE, various sorbents have been proposed, such as TiO 2 , 20 activated carbon, 21 Fe 3 O 4 nanoparticles, 22 micro crystalline naphthalene, 23 carbon nanotubes, 24 Amberlite XAD-7 resin, 25 activated alumina 26 and nanoporous silica. 27 Among these sorbents, nanoporous silicas, such as MCM--41, MCM-48 and SBA-15, have attracted great attention because of their adjustable morphology and porosity, potentiality of functionalization, high chemical stability in a great variety of media and temperatures, very high specific surface areas and the simplicity of their syntheses via the sol-gel method, which allows such materials to be obtained through mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%